Crustal Thickness Variation Across the Sea of Marmara Region, NW Turkey: A Reflection of Modern and Ancient Tectonic Processes. Issue 7 (27th June 2020) - Jenkins, J.; Stephenson, S. N.; Martínez‐Garzón, P.; Bohnhoff, M.; Nurlu, M.
Abstract: The Marmara region in Turkey is an important geological setting, both from a tectonic and a seismic hazard/risk perspective. We present a new map of crustal thickness variation across this complex region to better understand the interplay of past and present tectonic processes that have formed present‐day structure. Maps of crustal thickness are created using Ps converted phases and receiver function (RF) analysis of earthquakes recorded at all publicly available seismic stations and stations in the national monitoring network (run by AFAD Disaster and Emergency Management Authority Turkey). RFs are converted from time to depth using a local 3‐D full‐waveform tomographic model and are combined in multiphase common conversion point stacks. Direct P to S converted arrivals and associated multiples are mapped to produce continuous maps of the Moho discontinuity. Results show Moho depths ranging from 26–41 km with a regional trend of westward thinning reflecting the effects of the extensional regime in western Anatolia and the neighboring Aegean Sea. The thinnest crust is observed beneath the western end of the Sea of Marmara, attributed to transtensional basin opening. A distinct region of increased crustal thickness bounded by the West Black Sea Fault in the west, and the northern strand of the North Anatolian Fault in the south, defines the ancient crustal terrane of the Istanbul Zone. Isostatic arguments indicate that the thickened crust and lower elevation in the Istanbul Zone require it to be underlain by thicker lithosphere, a conclusion that is consistent with its hypothesized origin near the Odessa shelf. Key Points: We present a new regional map of Moho topography in the Marmara region, based on RF CCP stacks Westward crustal thinning reflects the effect of ongoing extension in western Anatolia and the neighbouring Aegean region Abrupt changes in crustal thickness define the non‐crustally compensated ancient terrane of the Instanbul block